Composite algae removal material and application thereof

Through the flocculation, sedimentation and bactericidal adsorption of composite algae removal materials, the toxicity and non-specific problems of harmful algae bloom treatment in the prior art are solved, and the efficient removal of algae and prevention of re-explosion of algae are achieved, which improves the algae removal effect and the feasibility of the material sex.

CN119240880AActive Publication Date: 2025-01-03YUNNAN UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411423497.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

In the prior art, when dealing with harmful algae blooms, chemical methods and coagulant precipitation methods have toxic problems, non-specificity and great impact on non-harmful algae bloom organisms, and it is difficult to apply on site on a large scale, and the algae may cause water dissolution after decay. The decline in oxygen and nutrient release promotes a relapse of algae.

Method used

Compound algae removal materials are used, composed of montmorillonite-carried chitosan nanofilaments and polyethylene glycol-grafted Ag-carried GO/CNC microspheres. Through flocculation and sedimentation and bactericidal adsorption, algae removal is synergistically removed and the efficiency of algae removal is improved. And through cross-linking, the barrier membrane is formed to prevent the algae from bursting again.

Benefits of technology

It has achieved efficient removal of harmful algae blooms, reduced the degradation of dissolved oxygen in water and the release of nutrients caused by algae decay, improved the algae removal effect, reduced the risk of algae eruption again, and the material is magnetic and easy to separate and filtration.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a composite algae removal material. The composite algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol grafted Ag-loaded GO / CNC microspheres, the preparation method comprises the following steps: respectively mixing montmorillonite-loaded chitosan nanowires and polyethylene glycol grafted Ag-loaded GO / CNC microspheres with water, preparing a montmorillonite-loaded chitosan nanowire solution and a polyethylene glycol grafted Ag-loaded GO / CNC microsphere solution, and sequentially spraying the two solutions on the surface of algae to remove the algae. The algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol grafted Ag-loaded GO / CNC microspheres, the two algae removal materials are sequentially added into an algae-containing water body, and the algae removal effect is improved through the synergistic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of algae control and treatment, and in particular to a composite algae removal material and application thereof. Background Art

[0002] In recent years, the frequency, intensity and scope of harmful algal blooms have been increasing worldwide, and the economic and ecological losses caused to marine ecosystems, aquaculture and tourism have become increasingly serious, which highlights the importance of finding efficient and environmentally friendly methods to prevent and control harmful algal blooms. The principle of emergency treatment of harmful algal blooms is to reduce the density of harmful algal bloom cells in the water body through certain technical means, thereby reducing its harm. Some countries and regions with frequent harmful algal blooms have conducted extensive research on the control measures of harmful algal blooms and explored some emergency treatment technologies and measures. The prevention and control measures of harmful algal blooms can be summarized as direct measures and indirect measures. Indirect measures include removing fish cages from the algal bloom outbreak area and stirring seawater to dilute the density of algal cells through measures such as aeration. However, there are currently no effective measures to deal with the toxicity of toxic algal bloom organisms to fish and shellfish. Direct strategies include the use of physical, chemical and biological methods to control harmful algal blooms. The chemical method is to use chemicals to directly kill algal bloom organisms or to use flocculation methods to precipitate algal cells from the water body to the bottom. The principle of direct killing is mainly through killing, such as using inorganic killing agents (such as copper sulfate, hydrogen peroxide, chlorine, sodium hypochlorite, sodium percarbonate and ozone) and organic algaecides (such as HDTMA, Sophorolipid and Aponin, etc.) to cause cell death. This type of method generally has the advantages of fast effect, convenient storage, transportation and operation, but some methods have major disadvantages. For example, the chemical agents used are mostly toxic substances, which are generally not specific and have a great impact on non-harmful algal bloom organisms. In addition, the lysis of toxic algae caused by chemical killing methods will cause toxins to enter the water body. The coagulant precipitation method uses flocculants such as inorganic coagulants, surfactants and polymer coagulants to cause harmful algal bloom organisms to condense and precipitate. Inorganic coagulants are mainly aluminum or iron compounds, such as aluminum sulfate and ferric chloride. Polymeric flocculants include inorganic polymer flocculants and organic polymer flocculants. Positively charged surfactants and polymer coagulants are most effective against harmful algal bloom organisms, but the high salinity of seawater usually greatly reduces their condensation effect. The coagulant precipitation method is effective when harmful algal blooms are dense, has a short action time, and has less impact on non-harmful algal blooms than the direct killing method. However, there are still some disadvantages in practical applications, such as difficulty in large-scale application on site. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a composite algaecidal material, which is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. The two algaecidal materials are added successively into algae-containing water bodies to improve the algaecidal effect through synergistic effect.

[0004] Technical solution: A composite algaecidal material, which is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Preferably, the method for preparing montmorillonite-loaded chitosan nanowires comprises the following steps: S11. After adding ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stirring to mix evenly, a cationic modified nano-montmorillonite is added and heated to react to obtain a magnetic montmorillonite; S12. Dissolving chitosan in an acetic acid solution to obtain a chitosan solution having a concentration of 5-8wt%; S13. Add the magnetic montmorillonite prepared in step S11 to the chitosan solution, prepare nanofiber bundles by electrostatic spinning, chop the nanofiber bundles to 0.5-2 mm, and then perform ultrasonic dispersion in a hydrochloric acid solution to obtain montmorillonite-loaded chitosan nanowires. Preferably, in the step S11, the mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 80-120 g: 250-350 g: 65-85 g: 25-35 g: 3000 mL, the temperature of the heating reaction is 180-230 ° C, and the time is 6-12 h. Preferably, in the step S13, the concentration of the magnetic montmorillonite in the chitosan solution is 3-6 wt%, the concentration of the hydrochloric acid solution is 0.01-0.1 mol / L, the ultrasonic power is 300-500 W, and the dispersion time is 100-300 min. Preferably, the method for preparing the polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions, and then dilute hydrochloric acid was added dropwise to separate the solution into layers, and the lower layer of GO / CNC microspheres was collected; S24. Add GO / CNC microspheres to 0.2-0.6 mol / L silver nitrate solution, stir thoroughly, and filter to obtain Ag+-loaded GO / CNC microspheres; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.1-0.5 mol / L trisodium citrate solution, heating the reaction, and obtaining Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 2-3:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 10-15h, and then dry at low temperature. After drying, esterification reaction is performed to obtain esterified Ag-loaded GO / CNC microspheres; S27. Add the esterified Ag-loaded GO / CNC microspheres to a polyethylene glycol aqueous solution, add stannous octoate, and heat to react to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Preferably, in step S23, the stirring speed is 400-800 r / min, and the stirring time is 2-6 h. Preferably, the temperature of the esterification reaction in step S26 is 120-160° C. and the time is 2-3 hours. Preferably, in step S27, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to polyethylene glycol is 1:10-20, the molecular weight of polyethylene glycol is 5000-8000, the heating reaction temperature is 80-100° C., and the time is 6-10 h. The above-mentioned composite algae removal material is applied by mixing montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres with water respectively to prepare montmorillonite-loaded chitosan nanowires solution and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres solution, and the two solutions are sprayed on the surface of algae successively to remove the algae. Preferably, the dosage of the algaecide material is as follows: the dosage of montmorillonite-loaded chitosan nanowires is 10-15 g per cubic meter of water, and the dosage of polyethylene glycol-grafted Ag-loaded GO / CNC microspheres is 5-10 g per cubic meter of water. Beneficial effects: The algae removal material of the present invention has the following advantages: 1. The algae removal material in the present invention is composed of two parts, one of which is montmorillonite-loaded chitosan nanowires, which is used as a flocculation and sedimentation material and plays a role in flocculation and sedimentation, and the other component is polyethylene glycol-grafted Ag-loaded GO / CNC microspheres as a bactericidal adsorption material and plays a bactericidal role; 2. In the present invention, cation-modified montmorillonite is selected, and magnetic materials are loaded between the interlayers of the cation-modified montmorillonite. The modified montmorillonite is then added to the chitosan spinning solution, and nanofiber bundles are prepared by electrostatic spinning. The fiber bundles are dispersed by ultrasonic dispersion to obtain nanofibers with an aspect ratio. The nanofibers loaded with montmorillonite can play a bridging role, which is beneficial to improving the algae removal efficiency of algae bloom organisms. The chitosan is also positively charged by acid treatment, so the montmorillonite-loaded chitosan nanofibers are positively charged as a whole, and can also have an "electrical neutralization" effect between negatively charged algae cells, and the algae removal efficiency is greatly improved. The clay in the present invention also has a certain magnetic property, which is convenient for the separation and filtration of the clay in the later stage. 3. After the algaecide flocculates the algae, the algae will undergo a decay process. If the algae decay quickly, it may cause a sharp drop in dissolved oxygen in the water, thereby affecting the survival of other organisms in the water. The decaying algae will also release free nutrients, such as nitrogen and phosphorus. These free nutrients may become the basis for the growth of a new generation of algae, thereby promoting the re-emergence of algae. The algaecide material of the present invention also contains polyethylene glycol grafted Ag-loaded GO / CNC microspheres. The cellulose spheres themselves have a porous structure, and the graphene oxide and silver contained in the microspheres can synergistically kill bacteria, and at the same time can adsorb free nutrients to prevent secondary outbreaks of algae; 4. The prepared montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres are separately prepared into solutions and added into water bodies successively. This is because after the polyethylene glycol-grafted Ag-loaded GO / CNC microspheres are prepared into aqueous solutions, the long chains of polyethylene glycol on the surface of the microspheres are opened, and the long chains can produce certain cross-linking and entanglement with the montmorillonite-loaded chitosan nanowires. When algae settle, the polyethylene glycol-grafted Ag-loaded GO / CNC microspheres will also settle, increasing the adsorption effect and reducing the risk of algae outbreak again. At the same time, when the montmorillonite-loaded chitosan nanowires and the polyethylene glycol-grafted Ag-loaded GO / CNC microspheres are cross-linked and entangled in the water body, the surface of the water body is equivalent to forming a barrier film, which affects its photosynthesis and accelerates the death of the algae. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A composite algae removal material, the algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres; The method for preparing montmorillonite-loaded chitosan nanowires comprises the following steps: S11. Add ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stir to mix evenly, then add cationic modified nano-montmorillonite and heat to react. The mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 80g:250g:65g:25g:3000mL. The heating reaction temperature is 180°C for 12h to obtain magnetic montmorillonite. S12. Dissolve chitosan in acetic acid solution to obtain a chitosan solution with a concentration of 5wt%; S13. The magnetic montmorillonite prepared in step S11 is added to the chitosan solution, wherein the concentration of the magnetic montmorillonite in the chitosan solution is 3 wt %, and a nanofiber bundle is prepared by electrospinning. The nanofiber bundle is chopped to 0.5-2 mm and then ultrasonically dispersed in a 0.01 mol / L hydrochloric acid solution. The ultrasonic power is 300 W and the dispersion time is 300 min to obtain montmorillonite-loaded chitosan nanowires. The method for preparing polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions at a stirring speed of 400 r / min for 6 h, and then dilute hydrochloric acid was added dropwise to separate the solution and collect the lower layer of GO / CNC microspheres; S24. Add GO / CNC microspheres to 0.2 mol / L silver nitrate solution, stir thoroughly, and filter to obtain Ag+-loaded GO / CNC microspheres; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.1 mol / L trisodium citrate solution, heating the solution to obtain Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 2:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 10 hours, and then dry at low temperature. After drying, perform an esterification reaction at a temperature of 160° C. for 2 hours to obtain esterified Ag-loaded GO / CNC microspheres; S27. The esterified Ag-loaded GO / CNC microspheres were added to a polyethylene glycol aqueous solution with a molecular weight of 5000, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to polyethylene glycol was 1:20, and stannous octoate was added. The reaction was heated at 80°C for 10 hours to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Example 2 A composite algae removal material, the algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres; The method for preparing montmorillonite-loaded chitosan nanowires comprises the following steps: S11. Add ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stir to mix evenly, then add cationic modified nano-montmorillonite and heat to react. The mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 120g:350g:85g:35g:3000mL. The heating reaction temperature is 230°C for 6h to obtain magnetic montmorillonite. S12. Dissolve chitosan in acetic acid solution to obtain a chitosan solution with a concentration of 8wt%; S13. The magnetic montmorillonite prepared in step S11 is added to the chitosan solution, wherein the concentration of the magnetic montmorillonite in the chitosan solution is 6 wt %, and a nanofiber bundle is prepared by electrospinning. The nanofiber bundle is chopped to 0.5-2 mm and then ultrasonically dispersed in a 0.01 mol / L hydrochloric acid solution. The ultrasonic power is 500 W and the dispersion time is 100 min to obtain montmorillonite-loaded chitosan nanowires. The method for preparing polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions at a stirring speed of 800 r / min for 2 h, and then dilute hydrochloric acid was added dropwise to separate the solution and collect the lower layer of GO / CNC microspheres; S24. Add GO / CNC microspheres to 0.6 mol / L silver nitrate solution, stir thoroughly, and filter to obtain Ag+-loaded GO / CNC microspheres; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.5 mol / L trisodium citrate solution, heating the solution to obtain Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 3:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 15 hours, and then dry at low temperature. After drying, perform an esterification reaction at a temperature of 120° C. for 3 hours to obtain esterified Ag-loaded GO / CNC microspheres; S27. The esterified Ag-loaded GO / CNC microspheres were added to a polyethylene glycol aqueous solution with a molecular weight of 8000, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to the polyethylene glycol was 1:10, and stannous octoate was added. The reaction was heated at 100°C for 6 hours to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Example 3 A composite algae removal material, the algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres; The method for preparing montmorillonite-loaded chitosan nanowires comprises the following steps: S11. Add ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stir to mix evenly, then add cationic modified nano-montmorillonite and heat to react. The mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 90g:280g:70g:26g:3000mL. The heating reaction temperature is 190°C for 10h to obtain magnetic montmorillonite. S12. Dissolve chitosan in acetic acid solution to obtain a chitosan solution with a concentration of 6wt%; S13. The magnetic montmorillonite prepared in step S11 is added to the chitosan solution, wherein the concentration of the magnetic montmorillonite in the chitosan solution is 4 wt %, and a nanofiber bundle is prepared by electrospinning. The nanofiber bundle is chopped to 0.5-2 mm and then ultrasonically dispersed in a 0.06 mol / L hydrochloric acid solution. The ultrasonic power is 350 W and the dispersion time is 150 min to obtain montmorillonite-loaded chitosan nanowires. The method for preparing polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions at a stirring speed of 500 r / min for 5 h, and then dilute hydrochloric acid was added dropwise to separate the solution and collect the lower layer of GO / CNC microspheres; S24. Add GO / CNC microspheres to 0.3 mol / L silver nitrate solution, stir thoroughly, and filter to obtain Ag+-loaded GO / CNC microspheres; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.2 mol / L trisodium citrate solution, heating the solution to obtain Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 2.2:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 15 hours, and then dry at low temperature. After drying, perform an esterification reaction at a temperature of 130° C. for 3 hours to obtain esterified Ag-loaded GO / CNC microspheres; S27. The esterified Ag-loaded GO / CNC microspheres were added to a polyethylene glycol aqueous solution with a molecular weight of 6000, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to polyethylene glycol was 1:12, and stannous octoate was added. The reaction was heated at 80°C for 9 hours to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Example 4 A composite algae removal material, the algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres; The method for preparing montmorillonite-loaded chitosan nanowires comprises the following steps: S11. Add ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stir to mix evenly, then add cationic modified nano-montmorillonite and heat to react. The mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 110g:320g:80g:32g:3000mL. The heating reaction temperature is 220°C and the time is 8h to obtain magnetic montmorillonite. S12. Dissolve chitosan in acetic acid solution to obtain a chitosan solution with a concentration of 7wt%; S13. The magnetic montmorillonite prepared in step S11 is added to the chitosan solution, wherein the concentration of the magnetic montmorillonite in the chitosan solution is 5wt%, and a nanofiber bundle is prepared by electrospinning. The nanofiber bundle is chopped to 0.5-2mm and then ultrasonically dispersed in a 0.02mol / L hydrochloric acid solution. The ultrasonic power is 450W and the dispersion time is 250min to obtain montmorillonite-loaded chitosan nanowires; The method for preparing polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions at a stirring speed of 700 r / min for 3 h, and then dilute hydrochloric acid was added dropwise to separate the solution and collect the lower layer of GO / CNC microspheres; S24. Add GO / CNC microspheres to 0.5 mol / L silver nitrate solution, stir thoroughly, and filter to obtain GO / CNC microspheres loaded with Ag+; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.4 mol / L trisodium citrate solution, heating the solution to obtain Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 2.6:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 10 hours, and then dry at low temperature. After drying, perform an esterification reaction at a temperature of 150° C. for 2 hours to obtain esterified Ag-loaded GO / CNC microspheres; S27. The esterified Ag-loaded GO / CNC microspheres were added to a polyethylene glycol aqueous solution with a molecular weight of 7000, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to polyethylene glycol was 1:18, and stannous octoate was added. The reaction was heated at 100°C for 7 hours to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Example 5 A composite algae removal material, the algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres; The method for preparing montmorillonite-loaded chitosan nanowires comprises the following steps: S11. Add ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stir to mix evenly, then add cationic modified nano-montmorillonite and heat to react. The mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 100g:300g:75g:28g:3000mL. The heating reaction temperature is 200°C and the time is 9h to obtain magnetic montmorillonite. S12. Dissolve chitosan in acetic acid solution to obtain a chitosan solution with a concentration of 6.5wt%; S13. The magnetic montmorillonite prepared in step S11 is added to the chitosan solution, wherein the concentration of the magnetic montmorillonite in the chitosan solution is 4.5wt%, and a nanofiber bundle is prepared by electrospinning. The nanofiber bundle is chopped to 0.5-2mm and then ultrasonically dispersed in a 0.04mol / L hydrochloric acid solution. The ultrasonic power is 400W and the dispersion time is 200min to obtain montmorillonite-loaded chitosan nanowires; The method for preparing polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions at a stirring speed of 600 r / min for 4 h, and then dilute hydrochloric acid was added dropwise to separate the solution and collect the lower layer of GO / CNC microspheres; S24. Add GO / CNC microspheres to 0.4 mol / L silver nitrate solution, stir thoroughly, and filter to obtain Ag+-loaded GO / CNC microspheres; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.3 mol / L trisodium citrate solution, heating the solution to obtain Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 2.4:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 12 hours, and then dry at low temperature. After drying, perform an esterification reaction at a temperature of 140°C for 2.5 hours to obtain esterified Ag-loaded GO / CNC microspheres; S27. The esterified Ag-loaded GO / CNC microspheres were added to a polyethylene glycol aqueous solution with a molecular weight of 8000, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to polyethylene glycol was 1:15, and stannous octoate was added. The reaction was heated at 85°C for 8 hours to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Comparative Example 1 The difference between Comparative Example 1 and Example 5 is that Comparative Example 1 contains only montmorillonite-loaded chitosan nanowires; Comparative Example 2 The difference between Comparative Example 2 and Example 5 is that Comparative Example 2 contains only GO / CNC microspheres grafted with polyethylene glycol and loaded with Ag; A composite algae removal material, the algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres; The method for preparing montmorillonite-loaded chitosan nanowires comprises the following steps: S11. Add ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stir to mix evenly, then add cationic modified nano-montmorillonite and heat to react. The mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 100g:300g:75g:28g:3000mL. The heating reaction temperature is 200°C and the time is 9h to obtain magnetic montmorillonite. S12. Dissolve chitosan in acetic acid solution to obtain a chitosan solution with a concentration of 6.5wt%; S13. The magnetic montmorillonite prepared in step S11 is added to the chitosan solution, wherein the concentration of the magnetic montmorillonite in the chitosan solution is 4.5wt%, and a nanofiber bundle is prepared by electrospinning. The nanofiber bundle is chopped to 0.5-2mm and then ultrasonically dispersed in a 0.04mol / L hydrochloric acid solution. The ultrasonic power is 400W and the dispersion time is 200min to obtain montmorillonite-loaded chitosan nanowires; The method for preparing polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions at a stirring speed of 600 r / min for 4 h, and then dilute hydrochloric acid was added dropwise to separate the solution and collect the lower layer of GO / CNC microspheres; S24. Add GO / CNC microspheres to 0.4 mol / L silver nitrate solution, stir thoroughly, and filter to obtain Ag+-loaded GO / CNC microspheres; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.3 mol / L trisodium citrate solution, heating the solution to obtain Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 2.4:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 12 hours, and then dry at low temperature. After drying, perform an esterification reaction at a temperature of 140°C for 2.5 hours to obtain esterified Ag-loaded GO / CNC microspheres; S27. The esterified Ag-loaded GO / CNC microspheres were added to polyethylene glycol with a molecular weight of 400, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to polyethylene glycol was 1:15, and stannous octoate was added. The reaction was heated at 85°C for 8 hours to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Comparative Example 4 A composite algae removal material, the algae removal material is composed of magnetic montmorillonite and polyethylene glycol grafted Ag-loaded GO / CNC microspheres; wherein the preparation method of the magnetic montmorillonite comprises the following steps: adding ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol, stirring and mixing them evenly, adding cationic modified nano-montmorillonite to heat and react, the mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 100g:300g:75g:28g:3000mL, the heating reaction temperature is 200°C, and the time is 9h, to obtain magnetic montmorillonite; The method for preparing polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions at a stirring speed of 600 r / min for 4 h, and then dilute hydrochloric acid was added dropwise to separate the solution and collect the lower layer of GO / CNC microspheres; S24. Add GO / CNC microspheres to 0.4 mol / L silver nitrate solution, stir thoroughly, and filter to obtain Ag+-loaded GO / CNC microspheres; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.3 mol / L trisodium citrate solution, heating the solution to obtain Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 2.4:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 10 hours, and then dry at low temperature. After drying, perform an esterification reaction at a temperature of 140° C. for 2.5 hours to obtain esterified Ag-loaded GO / CNC microspheres; S27. The esterified Ag-loaded GO / CNC microspheres were added to a polyethylene glycol aqueous solution with a molecular weight of 8000, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to polyethylene glycol was 1:15, and stannous octoate was added. The reaction was heated at 85°C for 8 hours to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres. Comparative Example 5 A composite algae removal material, the algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted GO / CNC microspheres; The method for preparing montmorillonite-loaded chitosan nanowires comprises the following steps: S11. Add ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stir to mix evenly, then add cationic modified nano-montmorillonite and heat to react. The mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 100g:300g:75g:28g:3000mL. The heating reaction temperature is 200°C and the time is 9h to obtain magnetic montmorillonite. S12. Dissolve chitosan in acetic acid solution to obtain a chitosan solution with a concentration of 6.5wt%; S13. The magnetic montmorillonite prepared in step S11 is added to the chitosan solution, wherein the concentration of the magnetic montmorillonite in the chitosan solution is 4.5wt%, and a nanofiber bundle is prepared by electrospinning. The nanofiber bundle is chopped to 0.5-2mm and then ultrasonically dispersed in a 0.04mol / L hydrochloric acid solution. The ultrasonic power is 400W and the dispersion time is 200min to obtain montmorillonite-loaded chitosan nanowires; The method for preparing polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions at a stirring speed of 600 r / min for 4 h, and then dilute hydrochloric acid was added dropwise to separate the solution and collect the lower layer of GO / CNC microspheres; S24. GO / CNC microspheres and citric acid in a mass ratio of 2.4:1 were added to water, and sodium hydroxide was added to adjust the pH of the solution to 3. The solution was allowed to stand at room temperature for 15 hours and then dried at low temperature. After drying, an esterification reaction was performed at a temperature of 140° C. for 2.5 hours to obtain esterified GO / CNC microspheres. S27. Add the esterified GO / CNC microspheres to a polyethylene glycol aqueous solution with a molecular weight of 8000, the mass ratio of the esterified GO / CNC microspheres to the polyethylene glycol is 1:15, and add stannous octoate. Heat the reaction at 85°C for 8 hours to obtain polyethylene glycol-grafted GO / CNC microspheres. The two components of the composite algae removal materials prepared in Examples 1-5 and Comparative Examples 3-4 were respectively prepared into solutions, and the sedimentation effect of the phagocytic golden ball algae was tested. In Examples 1-5 and Comparative Example 3, the dosage of montmorillonite-loaded chitosan nanowires per cubic water body was 15 g, and the dosage of polyethylene glycol-grafted Ag-loaded GO / CNC microspheres per cubic water body was 8 g. In Comparative Example 1, the dosage of montmorillonite-loaded chitosan nanowires per cubic water body was 15 g, and the dosage of polyethylene glycol-grafted Ag-loaded GO / CNC microspheres per cubic water body was 8 g. In Comparative Example 4, the dosage of magnetic montmorillonite per cubic water body was 15 g, and the dosage of polyethylene glycol-grafted Ag-loaded GO / CNC microspheres per cubic water body was 8 g. The dosage of GO / CNC microspheres with Ag grafted with polyethylene glycol is 8 g per cubic meter of water, the dosage of montmorillonite-loaded chitosan nanowires per cubic meter of water is 15 g, and the dosage of polyethylene glycol-grafted GO / CNC microspheres per cubic meter of water is 8 g; the difference in the addition method of Comparative Example 6 is that the preparation method in Comparative Example 6 is the same as that in Example 5, but when Comparative Example 6 is used, the magnetic montmorillonite and polyethylene glycol-grafted GO / CNC microspheres loaded with Ag are added to water at the same time to prepare a spray solution; the dosage of montmorillonite-loaded chitosan nanowires per cubic meter of water is 5 g, and the dosage of polyethylene glycol-grafted GO / CNC microspheres loaded with Ag per cubic meter of water is 8 g. The algae cell density of the Golden Globe Algae in the algae liquid used in the test was approximately 9.0×109cells / L-10.0×109cells / L. Table 1 shows the algae removal rate 24h removal rate / % 7d removal rate 30d removal rate Example 1 65.6 93.2 98.2 Example 2 62.9 92.1 97.5 Example 3 66.4 95.5 97.2 Example 4 69.1 94.8 98.5 Example 5 68.7 96.2 98.0 Comparative Example 1 68.2 95.6 89.6 Comparative Example 2 25.9 35.6 15.9 Comparative Example 3 56.9 75.8 85.3 Comparative Example 4 62.8 89.5 88.6 Comparative Example 5 66.9 93.6 88.5 Comparative Example 6 56.8 85.9 88.1 Comparative Example 7 57.9 85.1 89.4 Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A composite algae removal material, characterized in that: The algae removal material is composed of montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres.

2. The composite algae removal material according to claim 1, characterized in that: The preparation method of the montmorillonite-loaded chitosan nanowires comprises the following steps: S11. After adding ferric chloride hexahydrate, sodium acetate and polyethylene glycol to ethylene glycol and stirring to mix evenly, a cationic modified nano-montmorillonite is added and heated to react to obtain a magnetic montmorillonite; S12. Dissolving chitosan in an acetic acid solution to obtain a chitosan solution having a concentration of 5-8wt%; S13. Add the magnetic montmorillonite prepared in step S11 to the chitosan solution, prepare nanofiber bundles by electrospinning, chop the nanofiber bundles into 0.5-2 mm, and then disperse them by ultrasonic in a hydrochloric acid solution to obtain montmorillonite-loaded chitosan nanofilaments.

3. The composite algae removal material according to claim 2, characterized in that: In the step S11, the mass volume ratio of ferric chloride hexahydrate, sodium acetate, polyethylene glycol, montmorillonite and ethylene glycol is 80-120g:250-350g:65-85g:25-35g:3000mL, the heating reaction temperature is 180-230°C, and the time is 6-12h.

4. The composite algae removal material according to claim 2, characterized in that: In the step S13, the concentration of magnetic montmorillonite in the chitosan solution is 3-6wt%, the concentration of the hydrochloric acid solution is 0.01-0.1mol / L, the ultrasonic power is 300-500W, and the dispersion time is 100-300min.

5. The composite algae removal material according to claim 1, characterized in that: The preparation method of the polyethylene glycol-grafted Ag-loaded GO / CNC microspheres comprises the following steps: S21. dissolving cellulose in a sodium hydroxide / urea / water system to obtain a cellulose solution; S22. adding graphene oxide to water, uniformly dispersing by ultrasonication, and then adding to the cellulose solution to obtain a GO / CNC composite solution; S23. The GO / CNC composite solution was added to the liquid paraffin containing Span80 under stirring conditions, and then dilute hydrochloric acid was added dropwise to separate the solution into layers, and the lower layer of GO / CNC microspheres was collected; S24. Add GO / CNC microspheres to 0.2-0.6 mol / L silver nitrate solution, stir thoroughly, and filter to obtain Ag+-loaded GO / CNC microspheres; S25. Adding the Ag+-loaded GO / CNC microspheres to a 0.1-0.5 mol / L trisodium citrate solution, heating the reaction, and obtaining Ag-loaded GO / CNC microspheres; S26. Add Ag-loaded GO / CNC microspheres and citric acid in a mass ratio of 2-3:1 to water, add sodium hydroxide to adjust the pH of the solution to 3, let stand at room temperature for 10-15h, and then dry at low temperature. After drying, esterification reaction is performed to obtain esterified Ag-loaded GO / CNC microspheres; S27. Add the esterified Ag-loaded GO / CNC microspheres to a polyethylene glycol aqueous solution, add stannous octoate, and heat to react to obtain polyethylene glycol-grafted Ag-loaded GO / CNC microspheres.

6. The composite algae removal material according to claim 5, characterized in that: In step S23, the stirring speed is 400-800 r / min, and the stirring time is 2-6 h.

7. The composite algae removal material according to claim 5, characterized in that: The temperature of the esterification reaction in step S26 is 120-160° C. and the time is 2-3 hours.

8. The composite algae removal material according to claim 5, characterized in that: In the step S27, the mass ratio of the esterified Ag-loaded GO / CNC microspheres to polyethylene glycol is 1:10-20, the molecular weight of the polyethylene glycol is 5000-8000, the heating reaction temperature is 80-100° C., and the time is 6-10 h.

9. An application of the composite algae removal material as claimed in claim 1, characterized in that: Montmorillonite-loaded chitosan nanowires and polyethylene glycol-grafted Ag-loaded GO / CNC microspheres were mixed with water respectively to prepare a montmorillonite-loaded chitosan nanowire solution and a polyethylene glycol-grafted Ag-loaded GO / CNC microsphere solution, and the two solutions were sprayed on the surface of algae successively to remove the algae.

10. The use of the composite algae removal material according to claim 9, characterized in that: The dosage of the algae removal material is as follows: the dosage of montmorillonite-loaded chitosan nanowires is 10-15 g per cubic meter of water, and the dosage of polyethylene glycol-grafted Ag-loaded GO / CNC microspheres is 5-10 g per cubic meter of water.

Citation Information

Patent Citations

  • Preparation method of chitosan grafted copolymer flocculation-bactericide

    CN103864991A

  • Environment-friendly magnesium-ion modified montmorillonite tap water flocculant and application thereof

    CN103880136A

  • High-molecular chitosan composite flocculant

    CN106673165A

  • Chitosan-biomass composite for removing harmful cyanobacteria causing green algae and method for recycling same

    WO2023080743A1